Treatment of Residual, Recurrent, or Metastatic Intracranial Hemangiopericytomas With Stereotactic Radiotherapy Using CyberKnife - Huang, Lichao; Bai, Jingmin; Zhang, Yanyang; Cui, Zhiqiang; Zhang, Zhizhong; Li, Jiwei; Wang, Jinyuan; Yu, Xinguang; Ling, Zhipei; Qu, Baolin; Pan, Longsheng (Frontiers in Oncology, 2021)
Purpose: Hemangiopericytomas are aggressive tumors known for their recurrence. The purpose of this study was to evaluate the management of residual, recurrent，and metastatic intracranial hemangiopericytomas using CyberKnife（CK）stereotactic radiotherapy（SRT）. Materials and Methods: Data were collected from 15 patients (28 tumors；8 men and 7 women; 32–58 years) with residual, recurrent，or metastatic intracranial hemangiopericytomas，who were treated with stereotactic radiotherapy using Cybekinfe between January 2014 and August 2019. All patients had previously been treated with surgical resection. Initial tumor volumes ranged from 0.84 to 67.2 cm3, with a mean volume of 13.06 cm3. The mean marginal and maximum radiosurgical doses to the tumors were 21.1 and 28.76 Gy, respectively. The mean follow-up time for tumors was 34.5 months, ranging from 13 to 77 months. Results: 15 patients were alive after treatment, the mean post-diagnosis survival at censoring was 45.6 months (range 13-77 months). The volumes of the 28 tumors in the 15 followed patients were calculated after treatment. Postoperative magnetic resonance imaging reveaaled a mean tumor volume of 6.72 cm3 and a range of 0–67.2 cm3, with the volumes being significantly lower than pretreatment values. Follow-up imaging studies demonstrated tumor disappearance in 7 (25%) of 28 tumors, reduction in 14(50%), stability in 1 (3.57%), and recurrence in 6 (21.4%). Total tumor control was achieved in 22 (78.5%) of 28 tumors. The tumor grade and fraction time were not significantly associated with progression-free survival. Intracranial metastasis occurred in three patients, and extraneural metastasis in one patient. Conclusions: On the basis of the current results, stereotactic radiotherapy using CyberKnife is an effective and safe option for residual, recurrent and metastatic intracranial hemangiopericytomas. Long-term close clinical and imaging follow-up is also necessary.